Outcomes and benefits of pediatric cochlear implantation in children with additional disabilities: a review and report of family influences on outcomes - Cejas, Ivette (Pediatric Health Med Ther, 2015)
The number of children with hearing loss with additional disabilities receiving cochlear implantation has increased dramatically over the past decade. However, little is known about their auditory and speech and language development following implantation. The purpose of this review is to evaluate the effects of cochlear implantation on the most common genetic and developmental disorders in children with hearing loss. Benefits of cochlear implantation for children with autism spectrum disorder, developmental delay, CHARGE syndrome, cerebral palsy, learning disorders, Usher syndrome, Waardenburg syndrome, and attention deficit/hyperactivity disorder are reviewed. Our review indicates that children with hearing loss and additional disabilities benefit from cochlear implantation, especially when implanted early. Thus, early interventions seem as important for these children as for deaf children without additional disabilities. Comparisons of outcomes across these disabilities indicate that children with little to no cognitive impairment (eg, Waardenburg sydrome, attention deficit hyperactivity disorder) have better outcomes than those with greater deficits in intellectual functioning (eg, autism, CHARGE syndrome). In addition, parents of children with hearing loss and additional disabilities report higher levels of parenting stress and greater child behavior problems than those without comorbid diagnoses. However, these parents are as sensitive when interacting with their children as parents with typically developing children using cochlear implantation. Given these results, it is critical to evaluate these children’s developmental milestones to provide early implantation and intervention, appropriately counsel families regarding realistic expectations for the implant, and facilitate family adaptation.